Employees’ emotional awareness as an antecedent of organizational commitment—The mediating role of affective commitment to the leader - Santana-Martins, Marisa; Nascimento, José Luís; Sánchez-Hernández, Maria Isabel (Frontiers in Psychology, 2022)
Commitment has been perceived as a strategic topic in organizations due to its positive effect on retaining talent, increasing performance, or boosting employees’ innovative behavior. However there are many focis of commitment in the workplace, which has represented a challenge to human resources management, who need implement measures to improve the employee’s commitment. Recent research has suggested a need to conduct studies about commitment, namely antecedents and the relationship between different focis, to understand the dynamic and directionality between them. Hence, the purpose of this work is to analyze how employees’ emotional awareness relates with two focis of commitment (the leader and the organization), also assessing the mediating role of affective commitment to the leader. The study uses structural equation modeling and Lisrel to test the hypotheses considering the multidimensionality of organizational commitment (affective; normative; and continuance), employees emotional awareness (understanding self-emotions; self-control when facing criticism; and understanding others’ emotions), and the affective commitment to the leader, under the scope of Social Exchange Theory. The Mackinon’s Z Test was used to assess the mediation role of affective commitment to the leader. The sample is composed for 403 employees from two multinational companies. The results provide empirical evidence about the mediating role of affective commitment to the leader in the relationship between employees’ emotional awareness and organizational commitment, and the employees’ emotional awareness as an antecedent of commitment. The implications for theory and practice are discussed.